The different roles of proximity in multiple informal network relationships: evidence from the cluster of high technology applied to cultural goods in Tuscany. Issue 9 (21st October 2018) - Capone, Francesco; Lazzeretti, Luciana
Abstract: The role of proximity in innovation and inter-organisational networks has received increasing attention over the past decade. Despite the rich literature, most contributions principally focus on only one type of relationship and mainly consider formal relationships such as R&D partnerships, EU projects or patents. The aim of the study is to investigate the role of various forms of proximity in multiple informal inter-organisational relationships. The article focuses on two research questions: (i) How do the various forms of proximity influence the formation of different informal relationships? and (ii) What is the impact of social ties on relationships for innovation? ERGM is applied to measure the different impact of the proximities on three network relationships operating in the cluster of High Technology applied to Cultural Goods. The results underline the heterogeneous impact of various forms of proximity on the different relationships and the strong impact of social ties on innovation.